Respons Kekebalan Tubuh Ayam IPB D1 terhadap Infeksi Virus Penyakit Tetelo (Newcastle Disease) (IMMUNE RESPONSE OF IPB D1 CHICKEN AGAINST NEWCASTLE DISEASE VIRUS ) - Setyaningsih, Retno; Murtini, Sri; Poetri, Okti Nadia; Sumantri, Cece (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
Newcastle disease (ND) or Tetelo is an endemic poultry disease in Indonesia, and caused significant economic losses. Instead of diseases control programme has been carried out, ND outbreaks still occurs among poultry flock. IPB D1 chicken is a type of cross-breeding chickens between pelung-sentul crossbred chicken male and kampung-broiler crossbred chicken female, this chicken is genetically selected based on on body resistance to disease. The aim of our research is to study immune response of IPB D1 against ND infection. Fourty IPB D1 chickens were used in this study,  and divided into three groups : vaccinated group, unvaccinated group, control group. Vaccinated group received two time ND vaccination at age 10 weeks and booster at age 12 weeks. Unvaccinated and control group were remain not vaccinated. At age 13 weeks, vaccinated and unvaccinated group were challenge with ND virus (107 EID50/ml). Immune response were determined based on antibody titer which is measured by haemagglutination inhibition (HI) test and the profile of white blood cell of the chicken. Our result showed that both vaccinated and unvaccinated group has ND antibody titer e” log 24  at challenge time, and survived after challenge. White blood cell profile among all groups showed that lymphocites has the higher number than other leukocyte type.  It can be concluded that  IPB D1 chickens showed a good response against ND virus.